Treatment of BRAF-Mutated Metastatic Melanoma: Immunotherapy or Target Therapy? - Ana Sofia Rodrigues; Ana Brinca (Sociedade Portuguesa de Dermatologia e Venereologia, 2021)
Metastatic melanoma has been associated with a poor prognosis, with overall survival rates at 5 years of 10%. Until 2011, the only treatments available for metastatic melanoma were chemotherapy and immunotherapy with interleukin-2. The more in-depth knowledge about the molecular biology of melanoma and the identification of BRAF mutations, which are the most frequently found, allowed us to find new therapeutic targets that came to modify the prognosis of these patients. Currently, the treatments available for metastatic melanoma with BRAF mutation are immunotherapy with immunological checkpoint inhibitors (anti-PD-1 to anti-CTLA-4) and targeted therapy with BRAF inhibitors and MEK inhibitors. However, the first-line therapy to be instituted in these patients remains unknown.